Corpus callosum stroke with seizure as primary symptom - Ruiz, John Christopher V.; Ong, Marissa T. (International Journal of Research in Medical Sciences, 2023)
The corpus callosum is a large commissural fiber connecting the two hemispheres. The anterior communicating artery, pericallosal artery, and posterior pericallosal artery supply it. Stroke in this area is indeed rare, with an incidence rate of 0.9% to 2.8% per year. There were no documented seizure cases as a manifestation of corpus callosum stroke. We report a case of a 42-year-old right-handed male with a history of hypertension and heart failure who presented with focal motor seizure with intact awareness, alien hand syndrome, and hemianesthesia. His cranial magnetic resonance imaging (MRI) showed a corpus callosum stroke and focal delta slowing on electroencephalography (EEG). This study showed that the corpus callosum is a possible epileptogenic focus.